L'attualità del pensiero di Giuseppe Toniolo (Società e diritti, 2022)
In the opinion of the Author, the optimal configuration of economy and society proposed by G. Toniolo, according to the interpretation of Mons. Domenico Sorrentino, can be considered fully in line with the “responsible welfare” model proposed for an improvement of the social condition of Italy.